Gospel Allegiance: What Faith in Jesus Misses for Salvation in Christ - Bates, Matthew W. (Brazos Press, 2019)
Challenging popular misconceptions about the biblical gospel, Matthew Bates shows that it is different, wider, and more beautiful than we have been led to believe.